Аналіз виробничого процесу на основі методики статистичного вибіркового поточного контролю монтажу об’єктів будівництва (на прикладі ВАТ “ДБК-3“ м.Київ) - Савенко, В. І.; Коваль, Л. М.; Савенко, С. С. (Ways to Improve Construction Efficiency, 2013)
Quality of construction It is not dependent on a construction stage, and estimate it by various indicators: geometrical, physico - mechanical, physico - thermal, technological, operational, etc. the Important role play statistical methods at operational quality assurance which allow to eliminate in due time regular errors of measurements, to specify is minimum necessary, but enough of tests to introduce corrective amendments in parameters of technological process, to find out necessity of repair (stop) of cars and mechanisms, to warn workers about improvement of professional skill. Statistical regulation of quality includes following stages: 1. Measurement of indicators, calculation of statistical criteria. 2. Calculation of statistical characteristics of technological process. Determination of volume of sample. 3. Regulation of quality of technological process.